Effects of Resistance Training Overload Progression Protocols on Strength and Muscle Mass - Chaves, Talisson Santos; Scarpelli, Maíra Camargo; Bergamasco, João Guilherme Almeida; Silva, Deivid Gomes da; Medalha Junior, Ricardo Alessandro; Dias, Nathalia Fernanda; Bittencourt, Diego; Carello Filho, Paulo Cesar; Angleri, Vitor; Nóbrega, Sanmy Rocha; Roberts, Michael D.; Ugrinowitsch, Carlos; Libardi, Cleiton Augusto (International Journal of Sports Medicine, 2024)
The aim of this study was to compare the effects of progressive overload in resistance training on muscle strength and cross-sectional area (CSA) by specifically comparing the impact of increasing load (LOADprog) versus an increase in repetitions (REPSprog). We used a within-subject experimental design in which 39 previously untrained young persons (20 men and 19 women) had their legs randomized to LOADprog and REPSprog. Outcomes were assessed before and after 10 weeks of training. Muscle strength was assessed using the one repetition maximum (1RM) test on the leg extension exercise, and the CSA of the vastus lateralis was assessed by ultrasonography. Both protocols increased 1RM values from pre (LOADprog: 52.90±16.32 kg; REPSprog: 51.67±15.84 kg) to post (LOADprog: 69.05±18.55 kg, REPSprog: 66.82±17.95 kg), with no difference between them (P+>+0.05). Similarly, both protocols also increased in CSA values from pre (LOADprog: 21.34±4.71 cm²; REPSprog: 21.08±4.62 cm²) to post (LOADprog: 23.53±5.41 cm², REPSprog: 23.39±5.19 cm²), with no difference between them (P+>+0.05). In conclusion, our findings indicate that the progression of overload through load or repetitions can be used to promote gains in strength and muscle hypertrophy in young men and women in the early stages of training.
Keywords: muscle cross-sectional area; 1-RM; concentric muscle failure; strength training